2016
DOI: 10.1002/jor.23289
|View full text |Cite
|
Sign up to set email alerts
|

Rotator cuff repair using cell sheets derived from human rotator cuff in a rat model

Abstract: To achieve biological regeneration of tendon-bone junctions, cell sheets of human rotator-cuff derived cells were used in a rat rotator cuff injury model. Human rotator-cuff derived cells were isolated, and cell sheets were made using temperature-responsive culture plates. Infraspinatus tendons in immunodeficient rats were resected bilaterally at the enthesis. In right shoulders, infraspinatus tendons were repaired by the transosseous method and covered with the cell sheet (sheet group), whereas the left infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…The supraspinatus tendon was fixed between sandpaper using cyanoacrylate glue and held vertically in a custom clamp. Specimens were preconditioned from 0 to 5% strain at a rate of 1% strain/sec for five cycles, followed by a displacement ramp to failure at a rate of 1% strain/sec …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The supraspinatus tendon was fixed between sandpaper using cyanoacrylate glue and held vertically in a custom clamp. Specimens were preconditioned from 0 to 5% strain at a rate of 1% strain/sec for five cycles, followed by a displacement ramp to failure at a rate of 1% strain/sec …”
Section: Methodsmentioning
confidence: 99%
“…Specimens were preconditioned from 0 to 5% strain at a rate of 1% strain/sec for five cycles, followed by a displacement ramp to failure at a rate of 1% strain/sec. [21][22][23] Micro-CT Analysis Eight weeks after repair surgery (Surgery 2), eight rats per group were sacrificed and the bilateral humeral bones with SSp muscles were harvested. Specimens were fixed in 10% formalin for 48 h at room temperature.…”
Section: Biomechanical Testingmentioning
confidence: 99%
“…A growing number of studies have shown that factors that promote osteogenesis and inhibit bone resorption, such as osteoinductive growth factors [31,32,33], also positively affect tendon-bone healing [34]. Treatments that enhance angiogenesis can also positively accelerate tendon repair [34,35,36], improve osteogenesis [17,18,37,38] and chondrogenesis [39], and theoretically promote tendon-bone healing [34,40,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Treatments that enhance angiogenesis can also positively accelerate tendon repair [34,35,36], improve osteogenesis [17,18,37,38] and chondrogenesis [39], and theoretically promote tendon-bone healing [34,40,41,42]. However, the effects of ICA on tendon-bone healing remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in this study, we directly compared primary hTSPCs to the immortalized single cell-derived cell line hMSC-Scx by analyzing their expression profiles (tendon-, mesenchymal lineage-related and collagen cross-linking genes), migration patterns, and ability to self-assemble tendon-like three dimensional (3D) cell sheets [3]. Cell sheet formation is based on a natural establishment of cell–cell and cell–matrix connections during cell culture with subsequent folding into a 3D tube-like shape [15,16]. Cell sheet technology resembles a process very similar to native tissue morphogenesis during embryo development; it is scaffold-free, as it not only eliminates the need of natural and synthetic carriers, but also offers a model to study in vitro tenogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%